Microremains from El Mirón Cave human dental calculus suggest a mixed plant–animal subsistence economy during the Magdalenian in Northern Iberia. (August 2015) - Power, Robert C.; Salazar-García, Domingo C.; Straus, Lawrence G.; González Morales, Manuel R.; Henry, Amanda G.
Abstract: Despite more than a century of detailed investigation of the Magdalenian period in Northern Iberia, our understanding of the diets during this period is limited. Methodologies for the reconstruction of Late Glacial subsistence strategies have overwhelmingly targeted animal exploitation, thus revealing only a portion of the dietary spectrum. Retrieving food debris from calculus offers a means to provide missing information on other components of diet. We undertook analysis of human dental calculus samples from Magdalenian individuals (including the "Red Lady") at El Mirón Cave (Cantabria, Spain), as well as several control samples, to better understand the less visible dietary components. Dental calculus yielded a diverse assemblage of microremains from plant, fungal, animal and mineral sources that may provide data on diet and environment. The types of microremains show that the individuals at El Mirón consumed a variety of plants, including seeds and underground storage organs, as well as other foods, including possibly bolete mushrooms. These findings suggest that plant and plant-like foods were parts of her diet, supplementing staples derived from animal foods. As faunal evidence suggests that the Magdalenian Cantabrian diet included a large proportion of animal foods, we argue here for a mixed subsistence pattern. Highlights: Microremains from dental calculus indicate a mix plant–animal subsistence pattern for the "Red Lady". Rare microremain types (spores, non-silicified plant tissue) dominate the calculus profile. Fungal spores in dental calculus potentially indicate mushroom use.